2005
DOI: 10.1176/appi.ajp.162.2.214
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Meta-Analysis of Psychotherapy for PTSD

Abstract: The majority of patients treated with psychotherapy for PTSD in randomized trials recover or improve, rendering these approaches some of the most effective psychosocial treatments devised to date. Several caveats, however, are important in applying these findings to patients treated in the community. Exclusion criteria and failure to address polysymptomatic presentations render generalizability to the population of PTSD patients indeterminate. The majority of patients posttreatment continue to have substantial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

72
1,204
14
46

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,736 publications
(1,336 citation statements)
references
References 73 publications
72
1,204
14
46
Order By: Relevance
“…Although the effect size in our pilot study was large at two weeks post-treatment, we note that the effect size was not as large as in other intensive treatments (e.g. Ehlers et al, 2014) and in regular, weekly trauma-focused treatment (Bradley et al, 2005). Identifying the optimal treatment format and duration is a subject for further study.…”
Section: Resultscontrasting
confidence: 70%
See 3 more Smart Citations
“…Although the effect size in our pilot study was large at two weeks post-treatment, we note that the effect size was not as large as in other intensive treatments (e.g. Ehlers et al, 2014) and in regular, weekly trauma-focused treatment (Bradley et al, 2005). Identifying the optimal treatment format and duration is a subject for further study.…”
Section: Resultscontrasting
confidence: 70%
“…This effect should be placed in perspective, however, compared to previous meta-analyses of regular weekly treatments and other intensive treatment formats (e.g. Bradley et al, 2005; Ehlers et al, 2014; Hendriks et al, 2010). Bradley et al found that regular, weekly, trauma-focused treatment resulted in large effect sizes of 1.43.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Given the high incidence of (subsyndromal) PTSD symptoms in police officers (Carlier & Gersons, 1992) and insufficient response to currently available psychotherapies for PTSD (Bradley, Greene, Russ, Dutra, & Westen, 2005), revealing neurobiological mechanisms underlying the development and persistence of trauma-related psychopathology is highly relevant. The approach of our study has several noteworthy characteristics.…”
Section: Discussionmentioning
confidence: 99%